Dacie and Lewis practical haematology - Bain, Barbara J.; Lewis, Shirley Mitchell; Dacie, John Vivian (Elsevier Churchill Livingstone, 2012)
"Recognized worldwide as the standard reference work, Dacie & Lewis Practical Haematology is a must have reference for any haematology laboratory. It covers all of the techniques used in the investigation of patients with blood disorders, including the latest technologies as well as the tried and true manual methods of measurement. It discusses the principles of each test, possible causes of error, the rationale for choosing one method over another and the interpretation, significance and clinical relevance of these findings. Each chapter conforms to a template, providing quick access to key information."